Notes on Early Land Plants Today. 28. Transfers of some taxa to Lobatiriccardia (Aneuraceae, Marchantiophyta) - Nebel, Martin; Söderström, Lars; Hagborg, Anders; Konrat, Matt Von (Phytotaxa, 2013)
Furuki (1991) elevated Riccardia subgen. Lobatiriccardia Mizutani & Hattori (1957: 38) to genus level as Lobatiriccardia (Mizutani & Hattori 1957) Furuki (1991: 319). At the same time he transferred Aneura alterniloba (Hooker & Taylor 1844: 572) Taylor in Gottsche et al. (1846: 469) to his new genus. A molecular phylogenetic study confirmed this treatment (Preussing et al. 2010). However, two recently recognized varieties fromAustralia and a species fromNew Zealand were not transferred as they do not occur in the area treated by the monograph (Furuki 1991). They are transferred as follows: